John Bankhead Magruder : A Military Reappraisal - Settles, Thomas Michael, 1944- (Book collections on Project MUSE., 2009)
Of all the major figures of the Civil War era, Confederate General John Bankhead Magruder is perhaps the least understood. The third-ranking officer in Virginias forces, behind Robert E. Lee and Joseph E. Johnston, Magruder left no diary, no completed memoirs, no will, not even a family Bible. There are no genealogical records and very few surviving personal papers. It is not surprising, then, that much existing literature about Magruder is incorrect. In John Bankhead Magruder, an exhaustive biography that reflects more than thirty years of painstaking archival research, Thomas M. Settles reme.